Gulf Cooperation Council (GCC) : Energy Price Reforms in the GCC-What Can Be Learned From International Experiences?. (Policy Papers; Policy Paper, 2015)
Energy prices in the GCC countries are low by international standards. These low prices have co-existed with rapid economic development in the region over the past 50 years, but the costs of this policy have also risen in terms of very high energy usage per capita. Providing energy at low prices has also effectively absorbed resources that could otherwise have been invested in human and physical capital or saved for future generations. The implicit cost of low energy prices in the GCC, in terms of foregone revenue, is estimated to be around 5 percent of GDP (about 8 percent of non-oil GDP) this year. GCC countries have been embarking on energy price reform in recent years. The recent decision of the UAE to remove fuel subsidies is an important initiative. Nevertheless, energy prices are generally still below international levels and differ substantially across the GCC countries. In most countries, further steps are needed to raise energy prices to reduce the growth in energy consumption and to support the fiscal adjustment that is necessary in the current lower oil price environment. Evidence in this paper suggests the inflationary impact of higher energy prices in the GCC is likely to be small, and while there may be some adverse effect on growth in the near-term, over the longer-term the growth benefits should be positive. Given the low weight of energy products in the CPI, first round effects of higher energy prices should be limited, while well anchored inflation expectations should help prevent second-round effects. On growth, a gradual increase in energy prices should have a manageable impact on industrial activity, although energy intensive industries will be adversely affected and will need to adjust. In the longer-term energy price reforms could generate significant permanent real income gains for the economy as a whole. More broadly, international experiences suggest that the likelihood of success with energy price reforms increases if the reforms are:.